Bronchial Mucosa–Associated Lymphoid Tissue Lymphoma Staged by 11C-Methionine. (August 2018) - Annunziata, Salvatore; Cuccaro, Annarosa; Rizzo, Alessio; Chiesa, Silvia; D'Alò, Francesco
Abstract : Abstract: A 57-year-old man had a diagnosis of a bronchial mucosa–associated lymphoid tissue lymphoma in the left lung and monoclonal gammopathy. The patient underwent whole-body 11 C-methionine PET/CT, in order to evaluate the amino acid avidity of the lesion and to stage the bronchial mucosa–associated lymphoid tissue lymphoma. 11 C-methionine uptake was detected in the lung lesion and in the mediastinal lymph nodes.